Analisis Peran Lingkungan Kerja Dalam Meningkatkan Produktivitas Mengajar Guru Di SMPN 1 Majalaya - Dela Syafitri; Dedi Mulyadi; Sungkono (Jurnal Ekonomi dan Bisnis Digital, 2024)
A good working environment can increase teacher productivity in the classroom in providing knowledge to students. Things that can improve teacher teaching productivity are motivation, training, patience, and a good and supportive work environment. This study aims to improve teacher teaching productivity during learning. The research method used in this research isu sing a qualitative approach. The results of interviews that have been conducted in this study can be seen that to increase teacher teaching productivity can be through the renewal of the work environment both physically and non-physically. The existance of a physical work environment update can make students and teachers more comfortable and make it easier for both when learning is taking place, while the non-physical work environment can strengthen the relationship between teachers and superiors, teachers with teachres, and teachers with students. The existence of both physical and non-physical work environment can increase teacher productivity.